Draft Genome Sequence of the Oleaginous Yeast Cryptococcus curvatus ATCC 20509 - Close, Dan (Genome Announc, 2016)
Cryptococcus curvatus ATCC 20509 is a commonly used nonmodel oleaginous yeast capable of converting a variety of carbon sources into fatty acids. Here, we present the draft genome sequence of this popular organism to provide a means for more in-depth studies of its fatty acid production potential.